DAMPAK PERSETUJUAN WORLD TRADE ORGANIZATION TERHADAP KEBIJAKAN INVESTASI DAN PERDAGANGAN (Studi Kasus: Keberatan Anggota WTO Terhadap Undang-Undang Mineral dan Batu Bara No.4/2009) - Jessi Garfield Sawy (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2018)
This research studied the Effect of World Trade Organization on Investment and Trading Policy with A Case Study on the Member Countries’ Objection against Mineral and Coal Law Number 4 of 2009 using realism, international organization, international cooperation and international trading theory approaches.  The data employed consisted of primary and secondary data. Primary data was collected using interview method. Secondary data was obtained from literature, article, journal and other sources relevant to the research. The conclusion of research was that Indonesia was prosecuted in WTO’s dispute settlement agency as some WTO’s member countries were objected with the Mineral and Coal Law Number 4 of 2009 considered as not consistent with WTO’s provision. However, Indonesia declined it with the reason that it could increase the added value of Mineral and Coal product for the nation welfare. It indicated that in WTO’s International Organization every member country still had opportunity of defending the national interest.  Keywords: Multilateral Trading System, Investment Policy, and Mining Sector Trade, national interest